Variation for heterodimerization and nuclear localization among known and novel oil palm SHELL alleles. Issue 2 (28th January 2020) - Singh, Rajinder; Low, Eng‐Ti Leslie; Ooi, Leslie Cheng‐Li; Ong‐Abdullah, Meilina; Ting, Ngoot‐Chin; Nookiah, Rajanaidu; Ithnin, Maizura; Marjuni, Marhalil; Mustaffa, Suzana; Yaakub, Zulkifli; Amiruddin, Mohd Din; Manaf, Mohamad Arif Abdul; et al.
Summary: Oil palm breeding involves crossing dura and pisifera palms to produce tenera progeny with greatly improved oil yield. Oil yield is controlled by variant alleles of a type II MADS‐box gene, SHELL, that impact the presence and thickness of the endocarp, or shell, surrounding the fruit kernel. We identified six novel SHELL alleles in noncommercial African germplasm populations from the Malaysian Palm Oil Board. These populations provide extensive diversity to harness genetic, mechanistic and phenotypic variation associated with oil yield in a globally critical crop. We investigated phenotypes in heteroallelic combinations, as well as SHELL heterodimerization and subcellular localization by yeast two‐hybrid, bimolecular fluorescence complementation and gene expression analyses. Four novel SHELL alleles were associated with fruit form phenotype. Candidate heterodimerization partners were identified, and interactions with EgSEP3 and subcellular localization were SHELL allele‐specific. Our findings reveal allele‐specific mechanisms by which variant SHELL alleles impact yield, as well as speculative insights into the potential role of SHELL in single‐gene oil yield heterosis. Future field trials for combinability and introgression may further optimize yield and improve sustainability.